Doing Family on the Move : Highly-Skilled Migrants in Switzerland and Germany (2020)
This study analyses the division between the labour force work and the care work of couples of highly-skilled migrants settling in either the Lake Geneva region (Switzerland) and the Frankfurt Rhine-Main region (Germany). It combines Migration studies and Expatriation studies and adopts a critical and innova- tive theoretical framework. In order to develop such a framework, it does not only stress the “methodological individualism” and the “methodological nation- alism” but also introduces the “methodological economism” to deconstruct an essentialised distinction between migration and mobility. Drawing on this frame- work and based on 36 qualitative semi-directive interviews with highly-skilled migrants and 8 problem centred interviews with key-informants, the current study deals with the construction of gendered hierarchies between partners who are repeatedly on the move for professional reasons. It shows various ways of set- tling in a new region after a relocation that I subsume under the concept of “doing family on the move”. Specifically, the analysis reveals a form of settling which readily implies the possibility of a next move: a “motile” settling. This form of set- tling has serious consequences on the capacity of the partners to coordinate two professional careers. Through an analysis of the decision to move, the discourse about one’s family and the strategies concerning mobility, the empirical part shows the gendered consequences of “motility”. These consequences are articulated in a “mutually exclusive model” deepening the understanding of gendered hierarchies in career achievement, in the context of highly-skilled migration. While the male partners operate three parallel elements: an upward professional career, a family- life implying child(ren), and maintaining their availability to further unplanned relocations; the female partners can only coordinate two of these concurrently. This inequality exists in the way the partners divide the work between the labour force and the care work; as the male partners combine the three elements by exten- sively taking advantage of specific, and mostly invisible, care work that the female partner provides. This care work does not only include caregiving and housework but also what I call the “homemaking”; that is to recreate the necessary conditions for a family-life after a relocation.